Staphylococcal Scalded Skin Syndrome Treated with Homoeopathy—A Case Report - Parveen, Suraia (Homœopathic Links, 2019)
Staphylococcal scalded skin syndrome (SSSS) is an acute superficial blistering skin disorder caused by the exfoliative toxins produced by gram-positive bacteria Staphylococcus aureus which predominantly affects children and neonates and can cause serious morbidity and mortality. The diagnosis of SSSS is based on clinical findings and requires prompt medical treatment with proper hygiene and adequate diet to achieve successful result. Here, a case of a two and half years old girl is presented with a blistering skin syndrome for past 2 days without taking any conventional medicinal treatment. It was treated successfully with individualised homoeopathic medicines Rhus toxicodendron with dilution 50 millesimal potency 4 (Rhus tox 0/4) with supportive care. Within 6 days of treatment, the patient responded well to the homoeopathy medicine. All the symptoms and signs of staphylococcal skin blister lesions were healed completely within 10 days of treatment without development of any complications and recurrence. Homoeopathy treatment has a positive curative effect in bacterial blister skin lesions. This case report represents an alternative for the treatment of SSSS.
Keywords: staphylococcal scalded skin syndrome; homoeopathy; Rhus toxicodendron; LM potency